2012
DOI: 10.1371/journal.pone.0038599
|View full text |Cite
|
Sign up to set email alerts
|

Two Mechanisms Regulate Keratin K15 Expression In Keratinocytes: Role of PKC/AP-1 and FOXM1 Mediated Signalling

Abstract: BackgroundKeratin 15 (K15) is a type I keratin that is used as a marker of stem cells. Its expression is restricted to the basal layer of stratified epithelia, and the bulge in hair follicles. However, in certain clinical situations including oral lichen planus, K15 is induced in suprabasal layers, which is inconsistent with the role of a stem cell marker. This study provides insights into the mechanisms of K15 expression in the basal and differentiating keratinocytes.Methodology/Principal FindingsHuman kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 83 publications
1
37
1
2
Order By: Relevance
“…Previous studies suggest that ROS signaling might induce keratinocyte differentiation through the PKC/AP-1 pathway (24,25). Interestingly, SIRT3 gene expression might in turn also be regulated through AP-1 transcription factors (26), suggesting a possible regulatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that ROS signaling might induce keratinocyte differentiation through the PKC/AP-1 pathway (24,25). Interestingly, SIRT3 gene expression might in turn also be regulated through AP-1 transcription factors (26), suggesting a possible regulatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When fibronectin was replaced with laminin-332, the cells produced multilayers but did not attach to the membrane. It has been reported that methylcellulose (1.13 %) induced irreversible loss of keratinocyte proliferation but the effect could be reversed by fibronectin (Bose et al 2012). This finding may explain the dependence of our model on fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…By exploiting the aberrant expression of FOXM1 found in many human cancers,38 we have developed a novel molecular diagnostic system that quantify the levels of cell proliferation,38 differentiation,10 ageing,40 genomic instability,2, 14, 16, 17, 19 epigenetic11, 14 and stem cell reprogramming10, 13, 41, 42 as a collective basis for cancer diagnosis. Our proof‐of‐principal studies tested qMIDS on multiple cohorts of patients with HNSCC and demonstrated that the qMIDS assay is a practical, sensitive, objective, quantitative and customisable method for cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 cell cycle transcription factor is involved in cancer initiation,10–13 progression14–16 and metastasis,10, 17–19 and ultimately drug resistance 12, 20–23. Here, we exploited the value of FOXM1 (isoform B)‐orchestrated transcriptional changes in 14 target genes and 2 reference genes as a ‘molecular gauge’ to quantify malignancy status of tissue specimens using a highly sensitive absolute quantitative reverse transcription PCR (qPCR) method and demonstrate a prototype multibiomarker ‘quantitative molecular index diagnostic system’ (qMIDS) for squamous cell carcinoma (SCC) detection.…”
mentioning
confidence: 99%